Inventing Local Traditions, Becoming a Local Brand: Creators of Ludic Performances on a Croatian island - Škrbić Alempijević, Nevena (Array, 2008)
In Bol on the island of Brač Carnival customs play a significant role in the local community's self-identification. Their organizers inscribe connotations of "authenticity" into them, defining them as a local brand. The applicability of Carnival in promoting the place as a unique cultural destination is perceived by political decision-makers and tourism industry representatives. Individuals most active in winter Carnival are invited to arrange performances at various summer occasions, such as the fiesta, sports events, the closure of tourist season, etc. Lay theatre performances, based on motifs drawn from the Carnival context, have also been staged in Bol, oriented towards the tourist market. However, these events are not made only for external users: numerous local inhabitants define them as their own heritage.